Combined iron and magnesium isotope geochemistry of pyroxenite xenoliths from Hannuoba, North China Craton: implications for mantle metasomatism - Zhao, X.; Cao, H.; Mi, X.; Evans, Noreen; Qi, Y.; Huang, F.; Zhang, H. (Springer, 2017)
© 2017, Springer-Verlag Berlin Heidelberg. We present high-precision iron and magnesium isotopic data for diverse mantle pyroxenite xenoliths collected from Hannuoba, North China Craton and provide the first combined iron and magnesium isotopic study of such rocks. Compositionally, these xenoliths range from Cr-diopside pyroxenites and Al-augite pyroxenites to garnet-bearing pyroxenites and are taken as physical evidence for different episodes of melt injection. Our results show that both Cr-diopside pyroxenites and Al-augite pyroxenites of cumulate origin display narrow ranges in iron and magnesium isotopic compositions (δ 57 Fe = −0.01 to 0.09 with an average of 0.03 ± 0.08 (2SD, n = 6); δ 26 Mg = − 0.28 to −0.25 with an average of −0.26 ± 0.03 (2SD, n = 3), respectively). These values are identical to those in the normal upper mantle and show equilibrium inter-mineral iron and magnesium isotope fractionation between coexisting mantle minerals. In contrast, the garnet-bearing pyroxenites, which are products of reactions between peridotites and silicate melts from an ancient subducted oceanic slab, exhibit larger iron isotopic variations, with δ 57 Fe ranging from 0.12 to 0.30. The δ 57 Fe values of minerals in these garnet-bearing pyroxenites also vary widely (−0.25 to 0.08 in olivines, −0.04 to 0.25 in orthopyroxenes, −0.07 to 0.31 in clinopyroxenes, 0.07 to 0.48 in spinels and 0.31–0.42 in garnets). In addition, the garnet-bearing pyroxenite shows light δ 26 Mg (−0.43) relative to the mantle. The δ 26 Mg of minerals in the garnet-bearing pyroxenite range from −0.35 for olivine and orthopyroxene, to −0.34 for clinopyroxene, 0.04 for spinel and −0.68 for garnet. These measured values stand in marked contrast to calculated equilibrium iron and magnesium isotope fractionation between coexisting mantle minerals at mantle temperatures derived from theory, indicating disequilibrium isotope fractionation. Notably, one phlogopite clinopyroxenite with an apparent later metasomatic overprint has the heaviest δ 57 Fe (as high as 1.00) but the lightest δ 26 Mg (as low as −1.50) values of all investigated samples. Overall, there appears to be a negative co-variation between δ 57 Fe and δ 26 Mg in the Hannuoba garnet-bearing pyroxenite and in the phlogopite clinopyroxenite xenoliths and minerals therein. These features may reflect kinetic isotopic fractionation due to iron and magnesium inter-diffusion during melt–rock interaction. Such processes play an important role in producing inter-mineral iron and magnesium isotopic disequilibrium and local iron and magnesium isotopic heterogeneity in the subcontinental mantle.